Determinants of Basketball Match Outcome Based on Game-related Statistics - Canuto, S. C.; Bezerra de Almeida, M. (European Journal of Human Movement, 2022)
This study aimed to systematically review the current scientific literature on game-related statistics that better discriminate basketball winning and losing teams. A systematic search of the databases Web of Science, Scopus, SPORTDiscus, PubMed, Science Direct, Latindex, Google Schoolar and Scielo was performed. Keywords addressed discriminant analysis, game-related statistics, discriminant factors, determinant factors, game outcome, match analysis, winning and losing and basketball. Data from the 20 out of 532 articles were eligible to be extracted. SC values were considered relevant for analysis when =0.32, with cut-off points set as 0.71 (excellent), 0.63 (very good), 0.55 (good), 0.45 (fair), and 0.32 (poor). Based on these indicators, 8 articles were included for meta-analysis. Our results indicate that defensive rebound and assists are the discriminant factors that better differentiate winners from losers regardless of location, phase of competition or level of teams. Also, both indicators were the more prevalent winning/losing discriminant factors classified as good (SC = 0.46) or very good (SC = 0.56).